Viabilidade da disposição de lodo secundário da ETE de Araraquara (SP) em argissolo vermelho - de Brito, Ana Paula Ferreira [UNESP]; Fuess, Lucas Tadeu [UNESP]; Menegário, Amauri Antônio [UNESP]; Jiménez-Rueda, Jairo Roberto [UNESP]; Garcia, Marcelo Loureiro [UNESP] (My University, 2013)
In wastewater treatment the accumulation of solid materials (sludge) is commonly verified at the end of the processes, whose disposal is characterized as problematic and costly. Among the reuse forms of the sludge or biosolid generated in domestic wastewater treatment plants (DWTPs) land application is highlighted, as it recycles organic matter and nutrients to the environment. Based on the potential impacts associated to the biosolid disposal in soils, the objective of this paper was to assess the effects of the land application of the biosolid resulting from a DWTP located in the City of Araraquara (SP, Brazil). Thus, containers (lisimeters) containing the studied soil were built and distinct doses of sludge - 500 and 1500 grams of total solids (TS) per m2 - were applied in each tank. The lisimeters were exposed to ambient conditions and were monitored for four months. Five accumulative sludge applications were carried out. Rainwater infiltrated in the tanks were tested for the detection of metals and pathogenicity. The chemical composition of grasses eventually grown in the tanks was also analyzed for the detection of metals and their nutritional power. The analyses indicated the absence of pathogenic organisms in the percolated water. Regarding to the metal content in the water, the values obtained were above the detection limit of the equipment used and below the maximum allowable limits to classify freshwaters class I. In addition, it was observed an increase in soil fertility by the end of the applications. Thus, it was verified that the sampled sludge has potential for agricultural reuse, highlighting the need for implementing the recommended doses by the current legislation and the periodic monitoring of the applied areas.
Feasibility of disposal of sludge secondary ETE Araraquara (SP) in red ultisol
Keywords: Detection of metals; Land application; Pathogenicity; Sludge; Soil fertility